DOENÇA PERIODONTAL EM MULHERES NA PÓS-MENOPAUSA E SUA RELAÇÃO COM A OSTEOPOROSE - Bertulucci, Livia Almeida Barros (2010)
The Osteoporosis, defined as an age disorder, characterized for the decrease of bone mass and increase of breakings susceptibility, is the most common metabolicbone illness, affecting at least 30% of all postmenopausal women. The aim of this study was to make a quantitative periodontal condition analysis through a casecontrol study of post menopausal women and its relation with osteoporosis. The sample consisted of 99 postmenopausal women, divided in to three groups according with the avaliation of the mass bone: normal bone (G1 with N=45), osteopenia (G2 with N=31) and osteoporosis (G3 with N=23). There applied the indexes of clinical attachment level (CAL), gingival on pob (BOP), plaque index (PI) and probing depth (PD) for all participants. The periodontal condition data were submitted to the BioEstat 2.0 software using parametrical tests as analysis of variance (ANOVA) and Bonferroni test, using the significance level of 5%. The results shown that the women in postmenopausal with osteoporosis had presented high average in CAL (2,61 ± 0,43mm), as well as PD (2,80 ± 0,64 mm), BOP (72,8 ± 25,9 mm) and PI (72,9 ± 24,2 mm). After the accomplishment of the statistical treatment, it was observed that there was significant difference for the periodontal situation mainly between G1 and G3 and G2 and G3 groups, and still presented higher percentage of presence of the periodontitis, the osteoporosis women group. It was concluded that the periodontal conditions of the interviewed and analyzed postmenopausal women had revealed the relation between periodontitis and osteoporosis.